Hyper-performativity and early career teachers: interrogating teacher subjectivities in neoliberal educational assemblages. Issue 6 (2nd November 2022) - Lambert, Kirsten; Gray, Christina
ABSTRACT: This paper explores the hyper-performative expectations of early career teachers (ECTs) in the context of neoliberal education assemblages. The need to support and retain beginning teachers is a salient issue in the context of troubling rates of teacher attrition. The study explores how ECTs perceive teacher identities in response to national standards. Our research revealed that ECTs held concerning conceptions of 'quality teaching' that are largely constructed through discourses of competition and job insecurity. ECT subjectivities were heavily influenced excessive extra-curricular hours, high-stress environments, and performative school cultures. This paper concludes that hyper-performative expectations of ECTs and insecure patterns of employment contribute to teacher attrition.